Istri Pemberi Nafkah Utama dalam UU No. 1 Tahun 1974 Perkawinan Perspektif Maqāshid al-shari’ah Jasser Auda - Pangestu, Pujo; Asmawi; Ahmad Muhtadi Anshor (DIKTUM: Jurnal Syariah dan Hukum, 2026)
Background: In contemporary society, professional women are present in every field, from educators to heads of state. Consequently, the phenomenon of the wife becoming the main breadwinner within the family context is increasingly common. However, existing regulations, a prevailing patriarchal culture, and non-comprehensive religious interpretations often act as barriers. It is therefore crucial to re-examine the wife's role as the primary provider within the current legal framework. Purpose: This study aims to analyze the position of the wife as the main breadwinner within the legal framework of Law No. 1 of 1974 on Marriage, and to connect it with the objectives of Jasser Auda Maqashid al-Shari’ah, which emphasize justice, welfare, and the sustainability of the family in an increasingly dynamic society. Methods: The research method employed is a literature review using a qualitative and normative approach. Data are collected from legal sources (Law No. 1/1974), scientific literature, and Jasser Auda’s Maqashid al-Shari’ah perspective. The data are then analyzed to identify the relevance and applicability of these principles within the context of dynamic gender roles. Results: The findings indicate that the wife's role as the main breadwinner can be legally recognized and has positive implications for family welfare. The discussion highlights the importance of revising the understanding of gender norms within marriage law. Implication: It is recommended that there is a need for policy support aligned with Maqashid al-Shari’ah to revise gender norm understandings, thereby creating a more just and balanced environment for all family members, and ensuring the law does not discriminate against women Originality: This study offers a new jurisprudential perspective that critically integrates Jasser Auda’s Maqashid al-Shari’ah framework to reinterpret the wife's role as the main breadwinner within Marriage Law No. 1 of 1974 which currently poses potential barriers